The changing landscape of Africa’s fertilizer market: implications for research and policy - Liverpool-Tasie, L.S.O.; Gurmu, M.Y.; Mason, N.M.; Tambo, J.A. (2025)
This article synthesizes peer-reviewed studies on fertilizer demand and supply in Africa published from 2007 to 2024. This large body of literature is skewed toward fertilizer demand, with little emphasis on critical supply chain challenges such as high costs and logistics, nor does it focus on the rising importance of micro, small, and medium enterprises (e.g., agrodealers), fertilizer production, and blending in Africa. Additionally, most research has focused on a relatively small number of countries and on cereal crops, overlooking Africa’s geographic, crop, and dietary diversity. The article advocates for a broader research agenda that recognizes the recent dynamism in African fertilizer markets and challenges posed by climate change, conflict, and other shocks. It emphasizes the critical need for new and better-quality data for this research agenda to be executed and to provide empirical evidence-based guidance for more effective and efficient fertilizer use and, ultimately, enhanced agricultural productivity and sustainability on the continent.